Maternal-Gynecology and Pediatric Medical Health Resort deinstitutionalizing hospitals for women and children - Grafil, Patricia Anne L. (College of Architecture, University of the Philippines Diliman, 2015)
The Philippines has one of the youngest populations in Southeast Asia. And the government now recognizes the importance of capitalizing in healthcare for children - investing in vaccination, and allocating more budget for modernizing public pediatric hospitals. For decades, there has been a market for medical tourists in the Philippines, especially in East Asia. The country was even dubbed as a "medical tourism mecca" because of the highest standards of healthcare offered at a very competitive price. Though there are standards and guidelines provided for general hospital design, non specifically cater to maternal and pediatric patients. In the Philippines, there are only three hospitals that specialize on pediatric care and only one caters specifically to mothers -- all of these are located within Metro Manila. Hospitals design, up to this day, still remain experience and evidence-based. Due to rapidly emerging technologies, existing hospital design standards no longer support the efficiency of spaces, maternal care and advances in treating childhood diseases. Hospitals are also notorious for provoking fear and stress that can have long-term effects on developing children, therefore necessitating healthcare design to be less institutionalized and more patient and family-centered. This study explores the common hospital monolith and modifies it into a level 2 maternal and pediatric medical resort in Pililia, Rizal catering to locals and tourists alike. Instead of a typical block in a dense urban setting, this study presents a sprawling medical park amidst nature. Buildings also create a more familiar and less intimidating environment for children ; and a calming therapeutic environment to aid in childbirth.